Composites of poly[4-((p-tolylimino)methyl)phenyl acrylate] and the Ni-complex with aminated MWCNT: Thermal, electrical and magnetic investigation - Yilmaz, Serpil; Coskun, Mehmet (Taylor & Francis Inc, 2018)
Its nickel complex and a polyacrylate with side chain the Schiff base obtained from the condensation reaction of 4-hydroxybenzaldehide and p-toluidine, have been synthesized. The three-component composites were prepared using the polyacrylate, poly[4-((p-tolylimino) methyl) phenyl acrylate], its Ni-complex, and aminated MWCNT at three different percent (2%, 8% and 15% by wt). For characterization, FT-IR, 1H-NMR, SEM-EDX, SEM images and VSM (vibrating sample magnetometer) were used. The specific magnetic susceptibility for the Ni-complex is calculated as 3.0x10(-8) m(3)/kg from the slope of VSM straight line and the Ni-complex shows paramagnetic property. Thermal stabilities of the composites decreased compared with the polymer and Ni-complex. The AC conductivities of the samples increased with increasing frequency and increasing temperature. Frequency exponent of the equation connecting the AC conductivity to angular frequency was calculated as between 1.06 and 0.86 at 298K and between 0.97 and 0.71 at 320K, for all samples. Log sigma(ac) vs 1000/T straight lines were generated above and below the T-g temperature and the activation energies were calculated from the slopes as the values between 0.097 and 0.331eV below Tg and the values between 1.134 and 0.768eV above T-g.
Keywords: Schiff base; MWCNT; composite; electrical; magnetic; thermal